Injectable hydrogel as stem cell scaffolds from the thermosensitive terpolymer of NIPAAm/AAc/HEMAPCL - Lian S (Dove Medical Press, 2012)
Sheng Lian,1Yan Xiao,1 Qingqing Bian,1Yu Xia,2 Changfa Guo,2 Shenguo Wang,2 Meidong Lang11Shanghai Key Laboratory of Advanced Polymeric Materials, Key Laboratory for Ultrafine Materials of Ministry of Education, School of Materials Science and Engineering, East China University of Science and Technology, Shanghai, People's Republic of China; 2Department of Cardiac Surgery, Zhongshan Hospital, Fudan University and Shanghai Institute of Cardiovascular Diseases, Shanghai, People's Republic of ChinaAbstract: A series of biodegradable thermosensitive copolymers was synthesized by free radical polymerization with N-isopropylacrylamide (NIPAAm), acrylic acid (AAc) and macromer 2-hydroxylethyl methacrylate-poly(ε-caprolactone) (HEMAPCL). The structure and composition of the obtained terpolymers were confirmed by proton nuclear magnetic resonance spectroscopy, while their molecular weight was measured using gel permeation chromatography. The copolymers were dissolved in phosphate-buffered saline (PBS) solution (pH = 7.4) with different concentrations to prepare hydrogels. The lower critical solution temperature (LCST), cloud point, and rheological property of the hydrogels were determined by differential scanning calorimetry, ultraviolet-visible spectrometry, and rotational rheometry, respectively. It was found that LCST of the hydrogel increased significantly with the increasing NIPAAm content, and hydrogel with higher AAc/HEMAPCL ratio exhibited better storage modulus, water content, and injectability. The hydrogels were formed by maintaining the copolymer solution at 37°C. The degradation experiment on the formed hydrogels was conducted in PBS solution for 2 weeks and demonstrated a less than 20% weight loss. Scanning electron microscopy was also used to study the morphology of the hydrogel. The copolymer with NIPAAm/AAc/HEMAPCL ratio of 88:9.6:2.4 was bioconjugated with type I collagen for the purpose of biocompatibility enhancement. In-vitro cytotoxicity of the hydrogels both with and without collagen was also addressed.Keywords: thermoresponsive, N-isopropylacrylamide, biodegradable, bioreactive